Memulihkan Demokrasi Digital Melalui Model Connective Democracy Berbasis Pancasila - Giri Harto Wiratomo; Abdul Basit; Ryan Prayogi; Edwindha Prafitra Nugraheni (University of Muhammadiyah Malang, 2026)
The transformation of digital democracy in Indonesia demonstrates the paradox between increased public participation and low quality deliberation due to the dominance of reactive, emotional, and fragmented digital interactions. This study aims to analyze the dynamics of digital democracy in Indonesia and develop a conceptual model of connective democracy based on Pancasila values as an effort to strengthen the quality of democratic interactions. This study uses a qualitative approach with a case study design that focuses on digital democracy practices on various social media platforms in the 2025–2026 period. Data were collected through digital documentation and observations of public interactions, and analyzed using qualitative content analysis and reflexive thematic analysis to identify communication patterns and key themes. The results show that digital connectivity has not been accompanied by the quality of deliberative social relations, giving rise to a tendency towards reactive democracy and polarization. Connective democracy based on Pancasila offers a framework that emphasizes the importance of empathy, openness, and cross-perspective dialogue based on the values of divinity, humanity, unity, democracy, and social justice. The implications of this study indicate that strengthening digital democracy requires the integration of technology, ethics, and values-based civic education to build the quality of civilized public interactions. The conclusion of this research is that the resulting conceptual model emphasizes the importance of shifting from mere digital connectivity to meaningful connections as the foundation of inclusive and deliberative digital democracy in Indonesia.